Determinasi Digital Disruption terhadap Inovasi Competitive Advantage dan dampaknya pada Kinerja Bisnis UMKM Sektor Jasa, Industri Kreatif Kabupaten Jombang - Lik Anah, Lik Anah; Laili, Choirun Nisful; Mahfudiyanto, Mahfudiyanto; Ningsih, Lilis Sugi Rahayu (Universitas Hamzanwadi, 2024)
Data for 2022–2023 indicates that 215,626,156 individuals, or 78.19% of Indonesia's total population, have internet access. It is also known that around 9 million people purchase online at MSMEs that are already in operation. These numbers highlight the enormous potential for Indonesia's digital economy. The purpose of this study is to ascertain, using competitive advantage innovation as the deciding variable, how digital disruption affects the business performance of MSMEs in the service sector and creative industries. This study use structural equation modeling (SEM) as its methodology. All MSMEs in the Jombang district's creative and service sectors who have used digital media for business purposes make up the research's population. Purposive sampling was used in the sample process, with 125 MSMEs representing the MSME service sector and creative industry population in the Jombang area. The study's findings indicate that MSMEs' innovation competitive advantage is impacted by digital disruption by a factor of 13,458. The relationship between Competitive Advantage Innovation and MSME Business Performance is 4.524. The impact of digital disruption on MSME business performance is 9,193. The competitive advantage of disruption and innovation as a determinant of MSME business performance is 4.149